Effect of Foot and Mouth Diseases Vaccination on Basic Semen Quality Parameter in Bali Cattle - Prihatin, Koko Wisnu; Amaliya, Anny; Musaffak, Taufiq Ridwan; Rosyada, Zulfi Nur Amrina (Universitas Airlangga, 2023)
This study aimed to determine the effect of post foot and mouth diseases (FMD) vaccination on the basic semen quality in Bali cattle bulls. The data used in this study were semen collection data of 25 Bali cattle bulls at the National Artificial Insemination Centre (NAIC), Singosari. The paired sample t-test was performed to compare the response variable of individual motility (%), abnormality (%), spermatozoa concentration (x 106 cells), and semen volume (mL) from regular semen collection in post and pre-vaccination groups. The results showed no significant difference in semen individual motility (t(74) = -1.72, p = 0.95), abnormality (t(74) = 2.06, p = 0.98), spermatozoa concentration (t(74) = -4.35, p = 1.00), and semen volume (t(74) = -0.11, p = 0.54) in Bali cattle bulls before and after vaccination. This study concludes that the FMD's vaccination program for Bali cattle bulls did not have the potential to reduce the basic semen quality for Bali Cattle frozen semen production.